Association Between Duration of Untreated Psychosis and Frontostriatal Connectivity During Maintenance of Visuospatial Working Memory - Manivannan, Ashwinee (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
BACKGROUND: A longer duration of untreated psychosis (DUP) has been linked with poor clinical outcomes, as well as variation in resting-state striatal connectivity with central executive regions. However, the link between DUP and task-based activation of executive neurocognition has not previously been examined. The following fMRI study examined the association between DUP and both activation and frontostriatal functional connectivity during a visual working memory (WM) paradigm in patients with first-episode psychosis (FEP). METHODS: Patients with FEP (N=37) underwent fMRI scanning while performing a visual WM task. At the single-subject level, task conditions were modeled; at the group level, each condition was examined along with DUP. Activation was examined within the dorsolateral prefrontal cortex (DLPFC), a primary region supporting visual WM activation. Frontostriatal functional connectivity during the WM was examined via psychophysical interaction between the dorsal caudate and the DLPFC. Results were compared to a reference range of connectivity values in a matched group of healthy volunteers (N=25). Task performance was also examined in relation to neuroimaging findings. RESULTS: No significant association was observed between DUP and WM activation. Longer DUP showed less functional frontostriatal connectivity with the maintenance of increasing WM load. Results were not related to task performance measures, consistent with prior work. CONCLUSIONS: Our data suggest that DUP may affect frontostriatal circuitry that supports executive functioning. Future work is necessary to examine if these findings contribute to the mechanism underlying the relationship between DUP and worsened clinical outcomes.